Empowering Vocational Culture Through Educational Collaboration and Creative Programs in SMK Negeri 1 Samarinda - Eko Satrio, Muhammad Bagus; Sugianta Nirawana, I Wayan; Rahminah, Rahminah; Vonny, Gabriela Angle; Apriyanti, Rizky; Suciani, Noer; Shinta, Nabilla; Habibi, Ahmad; Attalla, Yasser Naufal (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
The community service program through integrated thematic real work lectures and teaching assistance at SMK Negeri 1 Samarinda aims to improve school culture dicipline and student involvement through a creative and collaborative approach. Students carry out various programs such as assessment supervision, collaboration on independence day competitions, morning pickets, school plan making, madding updates, and career seminars. This activity is carried out by observation methods, collaboration with the Student Council and supervisors, as well as direct practice inside and outside the classroom. The results of the activities show an increase in student discipline, creativity, and enthusiasm for learning and strengthen the synergy between students and schools. This program proves the importance of active involvement of students in the process of service-based education